Codes across languages at Kedai Inggris Coffee Shop: An autoethnography story - Andra Fakhrian; Maria Arina Luardini (Universitas Islam Sultan Agung, 2022)
This article discusses the successful methods used in English speaking classroom at Kedai Inggris Coffee Shop Sampit, a coursework taught by Andra Fakhrian. Thereof, the purpose of this research is to observe and learn the journey of the teacher got the admission and brought the students to be distinguished and fluent in performing English. A descriptive qualitative method and autoethnography approach are the tools to draw the analysis as this research is a self-study, that the analysis is elaborated in the form of narrative. Throughout the results of Autoethnography description, moreover, this article has found: 1) a role play model is the key to the technique used in the classroom, 2) code switching and mixing are often got through in order to build the engagement between teacher and students, yet it results the clear understanding towards the material.